Polarizing film, polarizing plate comprising same, and in-vehicle image display device comprising same
By using a thin polyvinyl alcohol resin film with high iodine concentration and adjusting the molar ratio of iodine to potassium, the problem of insufficient durability of the existing polarizing film in the heating environment is solved, and excellent optical characteristics and durability are achieved.
Patent Information
- Application Number
- CN202411897269.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-06-23
- Filing Date
- 2018-05-16
- Publication Date
- 2025-03-14
AI Technical Summary
The existing polarizing films are not durable in severe heating environments and are difficult to maintain excellent optical properties.
A polyvinyl alcohol resin film having a thickness of 8 μm or less was used as the polarizing film material, with an iodine concentration of 5.0% by weight or more, and the molar ratio (I/K) of the iodine concentration to the potassium concentration was adjusted to be 2.5 or less to inhibit the polyethyleneization reaction.
It realizes the maintenance of excellent optical characteristics and durability in severe heating environments, prevents the polarizing film from turning red, and is suitable for applications such as vehicle-based image display devices.
Smart Images

Figure CN119620278A_ABST
Abstract
Description
[0001] The present application is a divisional application of the Chinese invention application “Polarizing film, polarizing plate including the polarizing film, and vehicle-mounted image display device including the polarizing plate” with the application date of May 16, 2018 and the application number of 201880042023.5. Technical Field
[0002] The present invention relates to a polarizing film, a polarizing plate including the polarizing film, and a vehicle-mounted image display device including the polarizing plate. Background Art
[0003] In a typical image display device, a liquid crystal display device, polarizing films are arranged on both sides of a liquid crystal unit due to its image forming method. As a method for manufacturing a polarizing film, for example, a method of stretching a laminate having a resin substrate and a polyvinyl alcohol (PVA) resin layer and then performing a dyeing treatment to obtain a polarizing film on the resin substrate has been proposed (for example, Patent Document 1). This method can obtain a thinner polarizing film, so it can contribute to the thinning of image display devices in recent years and has attracted much attention. For such a thin polarizing film, further improvements in various properties and expansion of uses are still being sought.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-338329 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The main object of the present invention is to provide a polarizing film having excellent optical properties and excellent durability even in a severe heating environment. In addition, the present invention also provides a polarizing plate using such a polarizing film, and an in-vehicle image display device using such a polarizing plate.
[0009] Solutions to the problem
[0010] The polarizing film of the present invention is composed of a polyvinyl alcohol resin film having a thickness of 8 μm or less, the polyvinyl alcohol resin film containing iodine and potassium, the iodine concentration being 5.0 wt % or more, and the molar ratio (I / K) of the iodine concentration to the potassium concentration being 2.5 or less.
[0011] In one embodiment, after the polarizing film is placed at 100° C. for 120 hours, the single transmittance change ΔTs represented by the following formula is greater than 0.0%:
[0012] ΔTs(%)=Ts 120 -Ts0
[0013] Where Ts0 is the monomer transmittance before heating, Ts 120 It is the single body transmittance after heating for 120 hours.
[0014] In one embodiment, the single body transmittance Ts0 of the polarizing film is 43.0% or less.
[0015] According to another aspect of the present invention, a polarizing plate is provided, which comprises the polarizing film and a protective film disposed on at least one side of the polarizing film.
[0016] In one embodiment, the protective film is disposed only on one side of the polarizing film.
[0017] According to another aspect of the present invention, there is provided a vehicle-mounted image display device, which includes the above-mentioned polarizing plate.
[0018] Effects of the Invention
[0019] According to the present invention, by optimizing the molar ratio (I / K) of the iodine concentration to the potassium concentration in a thin polarizing film containing a high concentration of iodine, a polarizing film having excellent optical properties and excellent durability in a severe heating environment can be obtained. A polarizing plate using such a polarizing film can be suitably used for applications requiring durability in a severe heating environment (e.g., an in-vehicle image display device). BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a partition diagram showing the relationship between iodine concentration and I / K for explaining the mechanism of suppressing polyene formation by optimizing I / K in the embodiment of the present invention.
[0021] Figure 2 This is a graph showing the state of iodine in the polarizing film (relationship between wavelength and absorbance) by comparing a thick polarizer and a thin polarizing film for explaining the mechanism of suppressing polyene formation by optimizing I / K in the embodiment of the present invention.
[0022] Figure 3 This is a schematic cross-sectional view for explaining a polarizing plate according to one embodiment of the present invention.
[0023] Explanation of symbols
[0024] 10…Polarizing film
[0025] 20…Protective film
[0026] 100…Polarizer DETAILED DESCRIPTION
[0027] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0028] A. Polarizing film
[0029] The polarizing film of the present invention is composed of a polyvinyl alcohol-based resin (hereinafter referred to as “PVA-based resin”) film.
[0030] The PVA resin used to form the above-mentioned PVA resin film can adopt any appropriate resin. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be mentioned. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA resin is usually 85 mol%~100 mol%, preferably 95.0 mol%~99.95 mol%, and more preferably 99.0 mol%~99.93 mol%. The saponification degree can be calculated according to JIS K 6726-1994. By using a PVA resin with such a saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, there will be concerns about gelation.
[0031] The average polymerization degree of the PVA-based resin can be appropriately selected according to the purpose. The average polymerization degree is usually 1000 to 10000, preferably 1200 to 5000, and more preferably 1500 to 4500. It should be noted that the average polymerization degree can be obtained according to JIS K 6726-1994.
[0032] Polarizing films (PVA-type resin films) typically contain iodine. Polarizing films are essentially PVA-type resin films that have been oriented by adsorption of iodine. The iodine concentration in the PVA-type resin film is 5.0% by weight or more, preferably 5.0% by weight to 12.0% by weight, and more preferably 5.5% by weight to 10.0% by weight. According to the present invention, by optimizing the molar ratio (I / K) of iodine concentration to potassium concentration as described later, the durability of such a thin polarizing film containing a high concentration of iodine can be significantly improved, and in particular, it can be prevented from turning red in a harsh heating environment. It should be noted that the "iodine concentration" in this specification refers to the amount of all iodine contained in the polarizing film (PVA-type resin film). More specifically, iodine is present in the polarizing film in the amount of 1 - , I2, I3 - The iodine concentration in this specification refers to the concentration of iodine including all these forms. As described later, the iodine concentration can be calculated from the X-ray fluorescence intensity obtained by X-ray fluorescence analysis and the film (polarizing film) thickness.
[0033] The polarizing film (PVA-type resin film) typically further contains potassium. The potassium concentration in the PVA-type resin film is preferably 0.5% to 2.0% by weight, and more preferably 0.7% to 1.5% by weight. As long as the potassium concentration is within such a range, the molar ratio (I / K) of the iodine concentration to the potassium concentration described later can be easily controlled within the desired range. The potassium concentration can also be calculated based on the X-ray fluorescence intensity and the film (polarizing film) thickness obtained by X-ray fluorescence analysis. It should be noted that the potassium concentration in the polarizing film will change in conjunction with the iodine concentration, so simply setting the potassium concentration and the iodine concentration in appropriate ranges, respectively, cannot achieve the effect of the present invention. That is, in the present invention, optimizing the molar ratio (I / K) of iodine concentration to potassium concentration has technical significance.
[0034] In an embodiment of the present invention, the molar ratio (I / K) of the iodine concentration to the potassium concentration in the polarizing film (PVA-type resin film) is less than 2.5, preferably 1.5~2.5, and more preferably 1.7~2.5. According to the present invention, by optimizing I / K, the durability of the thin polarizing film containing a high concentration of iodine as described above can be significantly improved. In more detail, the iodine concentration in the thin polarizing film (for example, a thickness of less than 8 μm) is significantly higher than that in the thick polarizing film (for example, a thickness of more than 20 μm). If such a thin polarizing film is to obtain excellent optical properties (such as polarization degree), the iodine concentration in the PVA-type resin film (polarizing film) must be set to a very high value. If the iodine concentration becomes higher, the interaction between iodine and PVA-type resins will make polyene easier to proceed, and polyene can be suppressed by adjusting I / K.
[0035] Regarding the mechanism of inhibiting polyene formation by optimizing I / K, refer to Figure 1 and Figure 2 to be described in more detail. Polyeneization refers to a reaction in which a large number of double bonds (polyenes) are generated in PVA when the polarizing film is placed in a high temperature environment. Since the polyene formed in the PVA (polarizing film) has an absorption region in the visible light region and does not have dichroism, the monomer transmittance that is originally expected to have a higher value will be significantly reduced (that is, the ΔTs described later will be reduced to less than 0.0% (negative)). In addition, since the polyene mainly absorbs light on the short wavelength side, the hue of the polarizing film formed with the polyene will turn red (reddening of the polarizing film). It is known that the formation of a charge transfer complex with iodine present in PVA will promote polyeneization, which is a major problem for polarizing films composed of PVA and iodine as the basis. In particular, it will become a significant problem for thin polarizers with increased iodine density. At this time, in order to produce a thin polarizing film with high optical properties, it is necessary to maintain the absorption in the visible light region that can influence the optical properties. As a result, in a thin polarizing film with high optical properties, there is an absorption wavelength in the ultraviolet region below 380nm and is defined as free I -、Free I3 - The amount of iodine decreases ( Figure 2 ). If I - becomes less, then K as the counter cation + At this time, due to K + The total amount contained in the polarizing film is small, so its reduction rate is relatively large, and I / K becomes larger. In this way, if you want to achieve high optical properties for a thin polarizing film with a high iodine concentration, I / K becomes larger. The iodine in the polarizing film is PVA / I 3- Complex, PVA / I 5- The present inventors found that if I / K becomes high, the balance will be disrupted and polyene will easily occur. As a result, it was found that polyene can be suppressed by optimizing I / K. Figure 1 For thick polarizers (for example, with a thickness of 20 μm or more), the iodine concentration will not be as high as that of thin polarizing films, so the I / K that can be achieved with thick polarizers is smaller ( Figure 1 In other words, in thick polarizers, the polyene problem is not so important. It should be noted that in thick polarizers, it is essentially impossible to achieve an I / K value above a given value ( Figure 1 In addition, if you want to make a thin polarizing film in area B, the iodine concentration in the polarizing film will become too low, and the single transmittance will become too high, making it essentially unable to function as a polarizing film. Therefore, if you want to achieve the desired optical properties as a thin polarizing film, you need to Figure 1 The thin polarizing film in the lower right region C or the upper right region D. At this time, as described above, the polyeneization of the thin polarizing film in the region D where I / K is large will become significant, and the problem of reduced single transmittance and reddening may occur. Therefore, the thin polarizing film in the region C with high iodine concentration and controlled I / K becomes the polarizing film of the embodiment of the present invention. Such a mechanism for suppressing polyeneization involves the problem of reduced single transmittance and reddening of the thin polarizing film in a high temperature environment, which is the first insight obtained through the trial method for solving this problem, and has an unexpected excellent effect.
[0036] The above-mentioned polyeneization easily occurs at high temperatures above 100°C, and it is an important issue for applications that require durability in such high temperatures (such as vehicle-mounted applications). That is, when a thin polarizing film is used in an image display device that can be used in a harsh heating environment (such as a vehicle-mounted image display device), the above-mentioned effect will be significant. In the image display device, the warping of the polarizer becomes a major problem, and since the thin polarizing film (and the polarizer containing such a polarizing film) has the characteristic of less warping, the advantage of the thin polarizing film is greater in such an image display device. On the other hand, as mentioned above, the inventors of the present invention have found that polyeneization can be suppressed by optimizing I / K, thereby solving the problem of using a thin polarizing film in a harsh heating environment. In this way, by optimizing I / K, the newly discovered problem of its reddening in a harsh heating environment can be solved while maintaining the effect of less warping unique to the thin polarizing film. By solving this new problem, the commercial value of a thin polarizing film in an image display device (for example, an in-vehicle image display device) that can be used in a severe heating environment can be significantly improved, so solving this problem has a very excellent effect industrially.
[0037] I / K, iodine concentration and potassium concentration in the film are obtained by the following procedure: First, the X-ray fluorescence intensity (kcps) of a sample (e.g., a PVA-based resin film to which a certain amount of KI is added) with known thickness (μm), iodine concentration (wt%) and potassium concentration (wt%) is measured, and a correction curve is drawn. The correction curves of iodine concentration and potassium concentration in the film are respectively expressed by the following formulas:
[0038] (iodine concentration) = A x (X-ray fluorescence intensity) / (film thickness)
[0039] (Potassium concentration) = B x (X-ray fluorescence intensity) / (film thickness)
[0040] In the formula, A and B are constants that vary depending on the measuring device. For example, when using ZSX100e (measurement sample diameter: 10 mm) as the measuring device, A is "18.2" and B is "2.99"; when using ZSX PRIMUS II (measurement sample diameter: 20 mm) as the measuring device, A is "20.5" and B is "0.112". In addition, I / K is calculated using the following formula:
[0041] (I / K)[molar ratio]=C×(I / K)[intensity ratio]
[0042] In the formula, C is a constant that varies depending on the measuring device. For example, when the ZSX100e (measurement sample diameter: 10 mm) is used as the measuring device, C is "1.91"; when the ZSX PRIMUS II (measurement sample diameter: 20 mm) is used as the measuring device, C is "56.36".
[0043] The boric acid concentration in the PVA-based resin film is preferably 12% to 21% by weight, more preferably 15% to 20% by weight, and further preferably 17% to 20% by weight. As long as the boric acid concentration is within this range, cracking during heating can be significantly suppressed through a synergistic effect with the above-mentioned iodine concentration.
[0044] The thickness of the PVA resin film (polarizing film) is 8 μm or less, preferably 7 μm or less, and more preferably 6 μm or less. If a PVA resin film having such a thickness is to ensure a given optical property (such as polarization degree), the iodine concentration must be very high, so the effect of optimizing I / K is significant. On the other hand, the thickness of the PVA resin film is preferably 1.0 μm or more, and more preferably 2.0 μm or more.
[0045] After the polarizing film is placed at 100° C. for 120 hours, the single transmittance change ΔTs is preferably 0.0% or more. ΔTs is represented by the following formula:
[0046] ΔTs(%)=Ts 120 -Ts0
[0047] Where Ts0 is the monomer transmittance before heating, Ts 120 It is the single transmittance after heating for 120 hours. That is, the polarizing film of the embodiment of the present invention has the following characteristics: even when placed in a harsh heating environment at 100°C, the single transmittance does not decrease, or on the contrary increases. This means that in a harsh heating environment, the polyeneization of the thin polarizing film is suppressed. Such characteristics can be achieved by optimizing I / K as described above. ΔTs is preferably 0.0%~0.5%, and more preferably 0.0%~0.3%.
[0048] The above-mentioned polarizing film preferably exhibits absorption dichroism at any wavelength of 380nm~780nm. The monomer transmittance Ts0 of the polarizing film is preferably 43.0% or more, more preferably 40.0%~42.5%, and further preferably 41.0%~42.0%. The polarization degree of the polarizing film is preferably 99.9% or more, more preferably 99.95% or more, and further preferably 99.98% or more. By setting the monomer transmittance to a lower level and setting the polarization degree to a higher level, the contrast can be improved, and the black display can be displayed darker, so that an image display device with excellent picture quality can be realized. By optimizing I / K, such a high degree of polarization and excellent durability (preventing it from turning red in a harsh heating environment) can be taken into account.
[0049] B. Method for manufacturing polarizing film
[0050] The method for manufacturing the polarizing film typically includes: forming a PVA-based resin layer on one side of a resin substrate; and stretching and dyeing a laminate of the resin substrate and the PVA-based resin layer to form the polarizing film from the polyvinyl alcohol-based resin layer.
[0051] B-1. Formation of PVA-based resin layer
[0052] The PVA-based resin layer may be formed by any appropriate method. Preferably, a coating liquid containing a PVA-based resin is applied onto a resin substrate and dried to form a PVA-based resin film.
[0053] The material forming the resin substrate may be any appropriate thermoplastic resin. Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Of these, norbornene resins and amorphous polyethylene terephthalate resins are preferred.
[0054] In one embodiment, it is preferred to use an amorphous (non-crystallized) polyethylene terephthalate resin. Among them, it is particularly preferred to use an amorphous (not easily crystallized) polyethylene terephthalate resin. Specific examples of the amorphous polyethylene terephthalate resin include a copolymer further containing isophthalic acid as a dicarboxylic acid and a copolymer further containing cyclohexanedimethanol as a diol.
[0055] When the stretching method in aqueous solution is adopted in the stretching described later, the above-mentioned resin substrate will absorb water, and the water can play the function of a plasticizer for plasticization. As a result, the tensile stress can be greatly reduced, and it can be stretched at a high ratio, so that a better stretchability can be obtained than when stretched in a gas atmosphere. As a result, a polarizing film with excellent optical properties can be produced. In one embodiment, the water absorption of the resin substrate is preferably 0.2% or more, and more preferably 0.3% or more. On the other hand, the water absorption of the resin substrate is preferably 3.0% or less, and more preferably 1.0% or less. By using such a resin substrate, undesirable situations such as a significant decrease in dimensional stability during manufacturing and a deterioration in the appearance of the obtained polarizing film can be prevented. It can also prevent the substrate from breaking when stretched in an aqueous solution and the PVA-type resin layer from peeling off the resin substrate. In addition, the water absorption of the resin substrate can be adjusted, for example, by introducing a modifying group into the forming material. The water absorption is a value obtained according to JIS K 7209.
[0056] The glass transition temperature (Tg) of the resin substrate is preferably 170°C or less. By using such a resin substrate, the crystallization of the PVA-type resin layer can be suppressed, while the stretchability of the laminate is fully ensured. In addition, considering the use of water to plasticize the resin substrate and to stretch it well in an aqueous solution, it is more preferably 120°C or less. In one embodiment, the glass transition temperature of the resin substrate is preferably 60°C or more. By using such a resin substrate, it is possible to prevent the occurrence of undesirable conditions such as deformation of the resin substrate (such as unevenness, relaxation, wrinkles, etc.) when applying and drying a coating solution containing the above-mentioned PVA-type resin, thereby making a laminate well. In addition, the stretching of the PVA-type resin layer can be well performed at an appropriate temperature (for example, about 60°C). In another embodiment, when applying and drying a coating solution containing a PVA-type resin, the glass transition temperature can also be lower than 60°C as long as the resin substrate is not deformed. In addition, the glass transition temperature of the resin substrate can be adjusted, for example, by introducing a modifying group into the forming material and heating it with a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K7121.
[0057] The thickness of the resin substrate before stretching is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. If it is less than 20 μm, there is a concern that it is difficult to form a PVA-based resin layer. If it exceeds 300 μm, for example, when stretching in an aqueous solution, there is a concern that the resin substrate takes a long time to absorb water and that stretching requires an excessive load.
[0058] The coating solution is typically a solution obtained by dissolving the PVA resin in a solvent. As the solvent, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various diols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine can be cited. They can be used alone or in combination of two or more. Among these, water is preferred. The PVA resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. If it is such a resin concentration, a uniform coating film that is closely attached to the resin substrate can be formed.
[0059] Additives may also be added to the coating liquid. Examples of additives include plasticizers, surfactants, and the like. Examples of plasticizers include polyols such as ethylene glycol and glycerol. Examples of surfactants include nonionic surfactants. They can be used to further improve the uniformity, dyeability, and stretchability of the obtained PVA-type resin layer. In addition, examples of additives include easy-adhesion components. By using easy-adhesion components, the adhesion between the resin substrate and the PVA-type resin layer can be improved. As a result, undesirable situations such as the PVA-type resin film peeling off from the substrate can be suppressed, and the dyeing and stretching in aqueous solution described later can be performed well. The easy-adhesion component can be, for example, modified PVA such as acetoacetyl-modified PVA.
[0060] Any appropriate method may be adopted as the coating method of the coating liquid, and examples thereof include roll coating, spin coating, wire bar coating, dip coating, die coating, flow coating, spray coating, and knife coating (comma coating, etc.).
[0061] The coating and drying temperature of the coating liquid is preferably 50° C. or higher.
[0062] Before forming the PVA type resin layer, the resin substrate may be subjected to a surface treatment (e.g., corona treatment), or an easy-adhesion layer may be formed on the resin substrate. By performing such a treatment, the adhesion between the resin substrate and the PVA type resin layer may be improved.
[0063] The thickness of the PVA-based resin layer (before stretching) is preferably 3 μm to 20 μm.
[0064] B-2. Stretching
[0065] The laminate may be stretched by any appropriate method. Specifically, it may be fixed-end stretching or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rollers having different peripheral speeds). Free-end stretching is preferred.
[0066] The stretching direction of the laminate can be appropriately set. In one embodiment, the laminate is stretched along the length direction of the long laminate. In this case, a method of stretching the laminate by passing it between rollers with different circumferential speeds is typically adopted. In another embodiment, the laminate is stretched along the width direction of the long laminate. In this case, a method of stretching using a tentering stretching machine is typically adopted.
[0067] The stretching method is not particularly limited, and a stretching method in a gas atmosphere or a stretching method in an aqueous solution can be used. The stretching method in an aqueous solution is preferred. By stretching in an aqueous solution, the film can be stretched at a temperature lower than the glass transition temperature (representatively about 80° C.) of the resin substrate or the PVA-type resin layer, thereby suppressing the crystallization of the PVA-type resin layer while stretching at a high ratio. As a result, a polarizing film with excellent optical properties can be produced.
[0068] The stretching of the laminate can be performed in one stage or in multiple stages. When the stretching is performed in multiple stages, for example, the free end stretching and the fixed end stretching can be combined, or the stretching in the aqueous solution and the stretching in the gas atmosphere can be combined. When the stretching is performed in multiple stages, the stretching ratio (maximum stretching ratio) of the laminate described below is the product of the stretching ratios of each stage.
[0069] The stretching temperature of the laminate can be set to any appropriate value according to the forming material of the resin substrate, the stretching method, etc. When the stretching method in a gas atmosphere is adopted, the stretching temperature is preferably above the glass transition temperature (Tg) of the resin substrate, more preferably above the glass transition temperature (Tg) of the resin substrate + 10°C, and particularly preferably above Tg + 15°C. On the other hand, the stretching temperature of the laminate is preferably below 170°C. By stretching at such a temperature, the rapid development of crystallization of the PVA-type resin can be suppressed, thereby suppressing the adverse conditions caused by the crystallization (for example, hindering the orientation of the PVA-type resin layer due to stretching).
[0070] When the stretching method in aqueous solution is adopted, the liquid temperature of the stretching bath is above 60°C, preferably 65°C to 85°C, and more preferably 65°C to 75°C. As long as it is within the temperature, the dissolution of the PVA-type resin layer can be suppressed, and it can be stretched at a high ratio. Specifically, as mentioned above, in terms of the relationship with the formation of the PVA-type resin layer, the glass transition temperature (Tg) of the resin substrate is preferably above 60°C. At this time, if the stretching temperature is lower than 60°C, there is a concern that even if the plasticization of the resin substrate brought by water is considered, it cannot be stretched well. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-type resin layer, and there is a concern that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0071] When the stretching method in aqueous solution is adopted, it is preferred to immerse the laminate in a boric acid aqueous solution for stretching (stretching in a boric acid aqueous solution). By using a boric acid aqueous solution as a stretching bath, the PVA-type resin layer can be given rigidity that can withstand the tension applied during stretching and water resistance that is insoluble in water. Specifically, boric acid generates tetrahydroxyborate anions in an aqueous solution, which can be cross-linked with the PVA-type resin through hydrogen bonds. As a result, the PVA-type resin layer can be given rigidity and water resistance, and can be well stretched to produce a polarizing film with excellent optical properties.
[0072] The above-mentioned boric acid aqueous solution is preferably obtained by dissolving boric acid and / or borate in a solvent, i.e., water. In the present invention, the boric acid concentration is 3.5 wt % or less, preferably 2.0 wt % to 3.5 wt %, and more preferably 2.5 wt % to 3.5 wt %. If the boric acid concentration is within such a range, the obtained polarizing film can have both excellent optical properties and excellent durability and water resistance. In addition, in addition to boric acid or borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent can also be used.
[0073] If the dichroic substance (representatively iodine) is adsorbed on the PVA resin layer in advance by dyeing described later, it is preferred to add an iodide to the above-mentioned stretching bath (boric acid aqueous solution). By adding an iodide, the dissolution of iodine adsorbed on the PVA resin layer can be suppressed. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, titanium iodide, and the like. Among these, potassium iodide is preferred. In an embodiment of the present invention, potassium iodide is used as an iodide, and the concentration of potassium iodide in the stretching bath, dyeing bath (described later), cross-linking bath (described later) and cleaning bath (described later) is adjusted, thereby achieving the desired potassium concentration in the polarizing film (the result is the desired I / K). In addition, by adjusting the concentration of potassium iodide, the iodine concentration in the polarizing film can also be adjusted. The concentration of potassium iodide in the stretching bath is preferably 0.05 to 15 parts by weight relative to 100 parts by weight of water, and more preferably 0.5 to 8 parts by weight.
[0074] The stretching ratio (maximum stretching ratio) of the laminate is preferably 5.0 times or more relative to the original length of the laminate. Such a high stretching ratio can be achieved, for example, by adopting an aqueous solution stretching method (boric acid aqueous solution stretching). It should be noted that in this specification, "maximum stretching ratio" refers to the stretching ratio just before the laminate breaks, which is a stretching ratio that confirms the breakage of the laminate and is 0.2 lower than this value.
[0075] In one embodiment, the laminate is stretched in a gas atmosphere at a high temperature (e.g., above 95° C.), and then stretched in a boric acid aqueous solution and dyed as described below. Since such stretching in a gas atmosphere can be defined as a preliminary or auxiliary stretching relative to stretching in a boric acid aqueous solution, it is hereinafter referred to as "auxiliary stretching in a gas atmosphere".
[0076] By combining auxiliary stretching in a gas atmosphere, the laminate can sometimes be stretched at a higher ratio. As a result, a polarizing film with more excellent optical properties (such as polarization degree) can be produced. For example, when a polyethylene terephthalate resin is used as the above-mentioned resin substrate, compared to stretching only by stretching in a boric acid aqueous solution, stretching by combining auxiliary stretching in a gas atmosphere and stretching in a boric acid aqueous solution can be performed while suppressing the orientation of the resin substrate. As the orientation of the resin substrate increases, its tensile tension also increases, making it difficult to achieve stable stretching and causing breakage. Therefore, by stretching while suppressing the orientation of the resin substrate, the laminate can be stretched at a higher ratio.
[0077] In addition, by combining auxiliary stretching in a gas atmosphere, the orientation of the PVA type resin can be improved, and thus the orientation of the PVA type resin can be improved after stretching in a boric acid aqueous solution. Specifically, it is speculated that by using auxiliary stretching in a gas atmosphere to improve the orientation of the PVA type resin in advance, the PVA type resin can be easily cross-linked with boric acid when stretched in a boric acid aqueous solution, and the boric acid is stretched in a state where the boric acid becomes a node, thereby improving the orientation of the PVA type resin after stretching in a boric acid aqueous solution. As a result, a polarizing film with excellent optical properties (such as polarization degree) can be produced.
[0078] The stretching ratio of the auxiliary stretching in the gas atmosphere is preferably 3.5 times or less. The stretching temperature of the auxiliary stretching in the gas atmosphere is preferably above the glass transition temperature of the PVA-based resin. The stretching temperature is preferably 95°C to 150°C. In addition, the maximum stretching ratio when the auxiliary stretching in the gas atmosphere is combined with the stretching in the above-mentioned boric acid aqueous solution is preferably 5.0 times or more, more preferably 5.5 times or more, and further preferably 6.0 times or more relative to the original length of the laminate.
[0079] B-3. Staining
[0080] The dyeing of the PVA resin layer is typically performed by adsorbing iodine on the PVA resin layer. The adsorption method includes: immersing the PVA resin layer (laminated body) in a dyeing solution containing iodine; applying the dyeing solution on the PVA resin layer; spraying the dyeing solution on the PVA resin layer, etc. Preferably, the PVA resin layer (laminated body) is immersed in the dyeing solution. This is because iodine can be well adsorbed.
[0081] The dyeing solution is preferably an iodine aqueous solution. The amount of iodine is preferably 0.1 to 0.5 parts by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, it is preferred to add an iodide to the iodine aqueous solution. As described above, the iodine compound is preferably potassium iodide. In an embodiment of the present invention, potassium iodide is used as the iodide, and the concentration of potassium iodide in the stretching bath, dyeing bath, cross-linking bath (described later) and cleaning bath (described later) is adjusted, thereby achieving the desired potassium concentration in the polarizing film (the result is the desired I / K). In addition, by adjusting the concentration of potassium iodide, the iodine concentration in the polarizing film can also be adjusted. The amount of potassium iodide in the dyeing bath is preferably 0.02 to 20 parts by weight relative to 100 parts by weight of water, and more preferably 0.1 to 10 parts by weight. In order to inhibit the dissolution of PVA-type resins, the liquid temperature of the dyeing solution during dyeing is preferably 20°C to 50°C. When the PVA-type resin layer is immersed in the dyeing solution, in order to ensure the transmittance of the PVA-type resin layer, the immersion time is preferably 5 seconds to 5 minutes. In addition, the dyeing conditions (concentration, liquid temperature, immersion time) can be set in such a way that the polarization degree or monomer transmittance of the polarizing film finally obtained is within a given range. In one embodiment, the immersion time is set in such a way that the polarization degree of the obtained polarizing film is 99.98% or more. In another embodiment, the immersion time is set in such a way that the monomer transmittance of the obtained polarizing film is 43.0% or less. In any embodiment, the iodine concentration, potassium iodide concentration and immersion time in the dyeing solution can be adjusted so that the iodine concentration and potassium concentration in the obtained polarizing film are within the desired range.
[0082] The dyeing treatment may be performed at any appropriate time. When the above-mentioned aqueous solution stretching is performed, it is preferably performed before the aqueous solution stretching.
[0083] B-4. Other treatments
[0084] In addition to stretching and dyeing, the PVA resin layer (laminate) may be subjected to the treatments required for forming a polarizing film. The treatments used to form a polarizing film include insolubilization treatment, crosslinking treatment, cleaning treatment, drying treatment, etc. In addition, the number and order of these treatments are not particularly limited.
[0085] The above-mentioned insolubilization treatment is typically carried out by immersing the PVA-type resin layer (laminate) in an aqueous solution of boric acid. By implementing the insolubilization treatment, water resistance can be imparted to the PVA-type resin layer. The concentration of the aqueous solution of boric acid is preferably 1 to 4 parts by weight relative to 100 parts by weight of water. The liquid temperature of the insolubilization bath (aqueous solution of boric acid) is preferably 20°C to 50°C. The insolubilization treatment is preferably carried out before stretching in the aqueous solution and the above-mentioned dyeing treatment.
[0086] The cross-linking treatment is typically performed by immersing the PVA resin layer (laminate) in an aqueous boric acid solution. By implementing the cross-linking treatment, the PVA resin layer can be given water resistance. The concentration of the aqueous boric acid solution is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. In addition, when the cross-linking treatment is performed after the dyeing treatment, it is preferably further combined with an iodide. By combining an iodide, the dissolution of iodine adsorbed on the PVA resin layer can be suppressed. As described above, the iodine compound is preferably potassium iodide. In an embodiment of the present invention, potassium iodide is used as an iodide, and the concentration of potassium iodide in the stretching bath, the dyeing bath, the cross-linking bath, and the cleaning bath (described later) is adjusted, thereby achieving the desired potassium concentration in the polarizing film (the result is the desired I / K). In addition, by adjusting the concentration of potassium iodide, the iodine concentration in the polarizing film can also be adjusted. The amount of potassium iodide in the cross-linking bath is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. Specific examples of iodides are as described above. The liquid temperature of the cross-linking bath (boric acid aqueous solution) is preferably 20°C to 60°C. The cross-linking treatment is preferably performed before the stretching in the aqueous solution. In a preferred embodiment, the stretching in the gas atmosphere, the dyeing treatment and the cross-linking treatment are performed in this order.
[0087] The above-mentioned washing treatment is typically performed by immersing the PVA-based resin layer (laminated body) in an aqueous potassium iodide solution. The drying temperature of the above-mentioned drying treatment is preferably 30°C to 100°C.
[0088] As described above, a polarizing film is formed on the resin substrate.
[0089] C. Polarizer
[0090] Typically, the polarizing film is used in a state where a protective film is laminated on one or both sides thereof (ie, as a polarizing plate). Therefore, the present invention also includes a polarizing plate. Figure 3 1 is a cross-sectional view of a polarizer according to an embodiment of the present invention. The polarizer 100 shown in the figure has a polarizing film 10 and a protective film 20 disposed on one side of the polarizing film. In actual use, the polarizer has an adhesive layer as the outermost layer (located on the surface of the polarizing film 10 in the example shown in the figure). The adhesive layer is typically the outermost layer on the image display device side. A spacer is temporarily bonded to the adhesive layer in a peelable state to protect the adhesive layer until actual use, and can be formed into a roll.
[0091] Any appropriate resin film can be used for the protective film 20. The forming material of the film can include, for example, cellulose resins such as (meth) acrylic resins, cellulose diacetate, cellulose triacetate, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, ester resins such as polyethylene terephthalate resins, polyamide resins, polycarbonate resins, and copolymer resins thereof. It should be noted that "(meth) acrylic resin" refers to acrylic resin and / or methacrylic resin. In addition, the resin substrate described in the above item B can be used directly as a protective film without peeling off.
[0092] In one embodiment, the (meth)acrylic resin uses a (meth)acrylic resin having a glutarimide structure. The (meth) acrylic resin having a glutarimide structure (hereinafter also referred to as a glutarimide resin) is described in, for example, Japanese Patent Application Laid-Open Nos. 2006-309033, 2006-317560, 2006-328329, 2006-328334, 2006-337491, 2006-337492, 2006-337493, 2006-337569, 2007-009182, 2009-161744, and 2010-284840. These descriptions are incorporated herein by reference.
[0093] The thickness of the protective film is preferably 10 μm to 100 μm. The protective film is typically laminated on the polarizer via an adhesive layer (specifically, an adhesive layer, a pressure-sensitive adhesive layer). The adhesive layer is typically formed of a PVA-based adhesive or an active energy ray-curable adhesive. The pressure-sensitive adhesive layer is typically formed of an acrylic pressure-sensitive adhesive.
[0094] D. Image display device
[0095] The polarizer can be used in an image display device. Therefore, the present invention also includes an image display device. Representative examples of image display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, and quantum dot display devices. The polarizing film of the embodiment of the present invention and the polarizer using the polarizing film have significant effects in a harsh heating environment, so the image display device is preferably an image display device that can be used in a harsh heating environment. Representative examples of such an image display device include a vehicle-mounted image display device. The image display device can adopt a structure well known in the industry, so detailed description is omitted.
[0096] Example
[0097] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. In addition, the measuring methods of each characteristic are as follows.
[0098] 1. Iodine concentration, potassium concentration and I / K in PVA resin films
[0099] For the polarizing films obtained in the examples and comparative examples, the X-ray fluorescence intensity (kcps) was measured using an X-ray fluorescence analyzer (Rigaku, trade name "ZSX100E", measurement diameter: ψ10 mm). On the other hand, the thickness (μm) of the polarizing film was measured using a spectroscopic film thickness meter (Otsuka Electronics, trade name "MCPD-3000"). Based on the obtained X-ray fluorescence intensity and thickness, the iodine concentration (weight %) and potassium concentration (weight %) were calculated using the following formula.
[0100] (iodine concentration) = 18.2 × (X-ray fluorescence intensity) / (film thickness)
[0101] (Potassium concentration) = 2.99 × (X-ray fluorescence intensity) / (film thickness)
[0102] In addition, I / K was calculated using the following formula.
[0103] (I / K)[molar ratio]=1.91×(I / K)[intensity ratio]
[0104] In addition, the iodine concentration (weight %) and potassium concentration (weight %) were determined using the following formulas using another X-ray fluorescence analyzer (manufactured by Rigaku Corporation, trade name "ZSX-PRIMUS II", measurement diameter: ψ20 mm).
[0105] (iodine concentration) = 20.5 × (X-ray fluorescence intensity) / (film thickness)
[0106] (Potassium concentration) = 0.112 × (X-ray fluorescence intensity) / (film thickness)
[0107] In addition, I / K was calculated using the following formula.
[0108] (I / K)[molar ratio]=56.36×(I / K)[intensity ratio]
[0109] In this example, the measurement results of ZSX100E are used. It should be noted that the coefficient used to calculate the concentration varies depending on the measuring device, and the coefficient can be obtained using an appropriate calibration curve.
[0110] 2. Single body transmittance
[0111] The polarizers obtained in the examples and comparative examples were measured using a spectrophotometer (Murakami Color Research Institute Co., Ltd., product name "DOT-3"). The transmittance is the Y value obtained by compensating the visibility in accordance with the 2-degree field of view (C light source) of JIS Z 8701-1982. The measurement was performed before and after the heating test at 100°C and 120 hours, and ΔTs was calculated using the following formula. In the formula, Ts0 is the monomer transmittance before heating, and Ts 120 It is the single body transmittance after heating for 120 hours.
[0112] ΔTs(%)=Ts 120 -Ts0
[0113] 3. Turn red
[0114] The polarizing plates obtained in Examples and Comparative Examples were bonded to a glass plate via an adhesive, and a heating test was performed at 100° C. for 120 hours, and the appearances before and after the heating test were visually observed. Evaluation was performed based on the following criteria.
[0115] ○: No reddening was observed
[0116] △: Reddening is observed but the degree is not a problem in actual use
[0117] ×: Reddening is noticeable and is a problem in actual use
[0118] [Example 1]
[0119] As the resin substrate, a long strip of polyethylene terephthalate copolymer film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of 75° C. was used.
[0120] One side of the resin substrate was subjected to corona treatment (treatment conditions: 55W・min / m 2 ), and an aqueous solution containing 90 parts by weight of polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol %), 10 parts by weight of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410"), and 13 parts by weight of potassium iodide was coated on this corona-treated surface, and dried at 60°C to form a PVA-based resin layer with a thickness of 13 μm to produce a laminate.
[0121] The obtained laminate was subjected to free-end uniaxial stretching by 2.4 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 130° C. (auxiliary stretching in a gas atmosphere).
[0122] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by blending 4 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0123] Next, the resultant was immersed in a dyeing bath (an iodine aqueous solution containing 0.3 parts by weight of iodine and 2.0 parts by weight of potassium iodide per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds (dyeing treatment).
[0124] Next, the resultant was immersed in a crosslinking bath (boric acid aqueous solution obtained by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0125] Then, while the laminate was immersed in a boric acid aqueous solution (boric acid concentration: 3.0 wt %) at a liquid temperature of 70° C., it was uniaxially stretched in the longitudinal direction (length direction) between rolls having different peripheral speeds to a total stretch ratio of 5.5 times (stretching in aqueous solution).
[0126] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by blending 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0127] Thereafter, the laminate was dried in an oven maintained at 70° C. (drying treatment).
[0128] In this way, a polarizing film having a thickness of 5 μm was formed on the resin substrate.
[0129] A cycloolefin film (ZF-12 manufactured by Zeon Co., Ltd., Japan, with a thickness of 23 μm) was bonded to the surface of the obtained polarizing film (the surface opposite to the resin substrate) as a protective substrate (protective film) by an ultraviolet curing adhesive. Specifically, the curing adhesive was applied in such a way that the total thickness became 1.0 μm, and the bonding was performed using a roller machine. After that, ultraviolet rays were irradiated from the cycloolefin film side to cure the adhesive. Next, the resin substrate was peeled off to obtain a polarizing plate having a structure of a cycloolefin film (protective substrate) / polarizing film.
[0130] The iodine concentration, boric acid concentration, and I / K of the obtained polarizing film were determined as described above. Also, ΔTs of the obtained polarizing plate was determined as described above, and reddening was evaluated. The results are shown in Table 1.
[0131] [Example 2]
[0132] A polarizing film was obtained in the same manner as in Example 1 except that the amount of potassium iodide in the cleaning bath was 3 parts by weight. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0133] [Example 3]
[0134] A polarizing film was obtained in the same manner as in Example 1 except that the boric acid concentration during stretching in the aqueous solution was set to 3.5 wt % and Ts0 was set to 42.6 %. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0135] [Example 4]
[0136] A polarizing film was obtained in the same manner as in Example 3 except that the amount of potassium iodide in the cleaning bath was 2 parts by weight. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0137] [Example 5]
[0138] A polarizing film was obtained in the same manner as in Example 4 except that an acrylic resin film was used as the protective substrate. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0139] [Comparative Example 1]
[0140] A polarizing film was obtained in the same manner as in Example 1 except that the amount of potassium iodide in the cleaning bath was 2 parts by weight. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0141] [Comparative Example 2]
[0142] A polarizing film was obtained in the same manner as in Example 1 except that Ts0 was set to 41.7% and the amount of potassium iodide in the cleaning bath was set to 2 parts by weight. The obtained polarizing film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0143] [Comparative Example 3]
[0144] An attempt was made to produce a polarizing film with a thickness of 5 μm, an iodine concentration of about 3 wt%, and an I / K of about 2.3. However, only a film with a single transmittance of 47% and a polarization degree of 92% could be produced, which was extremely insufficient (i.e., essentially unable to function as a polarizing film).
[0145] [Reference Example 1]
[0146] A PVA-based resin film (manufactured by Kuraray, trade name "PS-7500", thickness: 75 μm, average polymerization degree: 2400, saponification degree 99.9 mol%) was immersed in a 30°C water bath for 1 minute and stretched 1.2 times in the transport direction, then immersed in a 30°C aqueous solution with an iodine concentration of 0.04 wt% and a potassium concentration of 0.3 wt% to dye it, and stretched it 2 times based on the completely unstretched film (original length). Then, the stretched film was immersed in a 30°C aqueous solution with a boric acid concentration of 4 wt% and a potassium iodide concentration of 5 wt%, and further stretched to 3 times based on the original length, then immersed in a 60°C aqueous solution with a boric acid concentration of 4 wt% and a potassium iodide concentration of 5 wt%, and further stretched to 6 times based on the original length, and then dried at 70°C for 2 minutes, thereby obtaining a polarizer with a thickness of 27 μm. The I / K of the polarizer is 1.6, the iodine concentration is 2.2% by weight, the potassium concentration is 0.5% by weight, and the single transmittance is 42.4%. Then, a PVA resin aqueous solution (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER (registered trademark) Z-200", resin concentration: 3% by weight) is applied on both sides of the polarizer, and a cycloolefin film (manufactured by Japan Zeon Co., Ltd., Zeonor ZB12, thickness: 50 μm) and a triacetylcellulose film (manufactured by Konica Co., Ltd., KC4UY, thickness: 40 μm) are attached to each side, and heated in an oven maintained at 60°C for 5 minutes to obtain a polarizer. The obtained polarizer is subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0147]
[0148] As is clear from Table 1, the polarizing films of Examples of the present invention have ΔTs of 0.0% or more (zero or positive), are thin, and can significantly suppress reddening.
[0149] Industrial Applicability
[0150] The polarizing film and polarizing plate of the present invention can be applied to image display devices such as liquid crystal display devices, organic EL display devices, and quantum dot display devices, and are particularly suitable for image display devices that can be used in severe heating environments (such as vehicle-mounted image display devices).
Claims
1. A polarizing film, comprising a polyvinyl alcohol resin film having a thickness of 8 μm or less, The polyvinyl alcohol resin film contains iodine and potassium. The iodine concentration is 5.0 wt % or more, and the molar ratio of iodine concentration to potassium concentration (I / K) is 1.5 to 2.5, The polarizing film has a single body transmittance Ts0 of 40.0% or more and 42.6% or less.
2. The polarizing film according to claim 1, wherein after being left at 100° C. for 120 hours, the single-unit transmittance change ΔTs represented by the following formula is 0.0% or more, ΔTs(%)=Ts 120 -Ts0 Where Ts0 is the monomer transmittance before heating, Ts 120 It is the single body transmittance after heating for 120 hours. 3 . A polarizing plate comprising the polarizing film according to claim 1 or 2 and a protective film provided on at least one side of the polarizing film.
4. The polarizing plate according to claim 3, wherein: The protective film is disposed only on one side of the polarizing film. 5 . An in-vehicle image display device comprising the polarizing plate according to claim 3 or 4 .
Citation Information
Patent Citations
Polarizing plate and its production
JP2000338329A
Method for manufacturing film for optics
JP2006309033A
Polarizer protective film, and polarizing plate using the same
JP2006317560A
Base material for surface-protective film and surface-protective film
JP2006328329A
Resin composition, optical film and polarizer protection film using the same
JP2006328334A